Step-Efficient Access to Chiral Primary Amines - Nugent, Thomas C.; Marinova, Sofiya M. (Synthesis, 2013)
Routes to enantioenriched amines are outlined that employ reductive amination and carbanion addition methods. The strategies require either one or two reaction steps from prochiral carbonyl compounds for the synthesis of the corresponding chiral primary amines.
Keywords: chiral amine; enantiopure amines; reductive amination; cuprate addition; imine reduction